Application of the Culturally Responsive Teaching (CRT) Approach Based on the Ludo Game to Increase the Learning Activeness of Class IX Abat Students of SMP Negeri 1 Palu in Civics Subjects - Antuntu, Nur’ain; Amus, Sunarto; Purwaningsih, Cici (CV. Rayyan Dwi Bharata, 2025)
This study aims to analyze the implementation of the Culturally Responsive Teaching (CRT) approach based on the Ludo game to enhance the learning activity of class IX Abat students at SMP Negeri 1 Palu in the Civics Education (PPKn) subject. The research method used is Classroom Action Research (CAR) with two cycles, each consisting of planning, implementation, observation, and reflection. The results of the study showed that the application of the CRT approach based on the Ludo game improved students' learning engagement. In Cycle I, student involvement was recorded at 70%, which increased to 85% in Cycle II. Moreover, integrating local cultural values into the game also contributed to students' understanding of Pancasila values. This study suggests the use of a culture-based approach in learning to enhance student motivation and participation.